2013
DOI: 10.7205/milmed-d-13-00047
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Blood Product Transfusion by U.S. Army MEDEVAC During Combat Operations in Afghanistan: A Process Improvement Initiative

Abstract: U.S. Army flight medics performed a process improvement initiative of 15 blood product transfusions on select Category A (Urgent) helicopter evacuation casualties meeting approved clinical indications for transfusion. These transfusions were initiated from point of injury locations aboard MEDEVAC aircraft originating from one of two locations in southern Afghanistan. All flight medics executing the transfusions were qualified through a standardized and approved program of instruction, which included day and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 19 publications
(1 reference statement)
0
37
0
Order By: Relevance
“…Both US and UK medevac platforms have implemented prehospital RBC transfusion capabilities for casualties at the point of wounding. (18, 19) Survival for these advanced platforms including prehospital RBC transfusion is greater than predicted. (35) An evaluation of advanced en-route prehospital capabilities demonstrated a 37% reduction in 30-day mortality among casualties with ISS>15.…”
Section: Discussionmentioning
confidence: 99%
“…Both US and UK medevac platforms have implemented prehospital RBC transfusion capabilities for casualties at the point of wounding. (18, 19) Survival for these advanced platforms including prehospital RBC transfusion is greater than predicted. (35) An evaluation of advanced en-route prehospital capabilities demonstrated a 37% reduction in 30-day mortality among casualties with ISS>15.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 There are promising reports of military and civilian experiences in which the feasibility and potential benefits of such protocols are shown. 2,8,21 However, ideal practice and the optimal ratio of components for prehospital administration are yet to be established. 19…”
Section: Discussionmentioning
confidence: 99%
“…15 Military data have demonstrated that more than 90% of potentially survivable casualties die from hemorrhage and MEDEVAC platforms from the United States and the United Kingdom have PH RBC transfusion capabilities. 1618 A recent report examining these advanced medical transport platforms demonstrated a 37% reduction in 30-day mortality for casualties with an injury severity score (ISS) of more than 15 when compared with conventional MEDEVAC platforms. 19 The authors note that 15% of patients overall received PH RBC transfusion, and among those with ISS of more than 15, a third of casualties received PH RBC transfusion.…”
mentioning
confidence: 99%